Interactions of Key Factors Affecting the Implementation of Integrated Project Delivery in the Global Construction Industry: A Systematic Review - Bin Asad, Saad; Mahesh Babu, Purushothaman; Poshdar, Mani (Emerald, 2025)
Purpose Integrated project delivery (IPD) is an approach that integrates people, systems, business structures and practices into a process that collaboratively utilises the skills and opinions of all project participants to enhance sustainability through waste reduction. Though numerous articles on factors related to IPD are available, the interactions between factors associated with IPD are a research gap. This study addresses this research gap and aims to identify the interactions between key factors of IPD. Design/methodology/approach A systematic literature review (SLR) was conducted using three databases and key publishers – Scopus, Emerald and ScienceDirect. The SLR identified 222 factors related to IPD by studying 66 articles. The factors were uploaded to VOSViewer to identify the critical factors through repetition. Each of the 66 articles was examined to determine the interactions between factors through deductive reasoning. The interactions were visualised using VENSIM, and analysis methods such as nodes, degree of centrality and eigenvector centrality were used to identify the critical factors of IPD. Findings A total of 127 factors were identified, of which mutual respect and trust, resistance to change, challenging cultural paradigms, client/owner’s resistance to change, difficulties in achieving financial transparency, interoperability and cost estimation challenges were deemed critical factors of IPD. The implications of this research will aid researchers and industry practitioners in comprehensively understanding the interactions between key factors, thus preparing solutions to increase IPD implementation for sustainable construction in the global context. Originality/value This study is the first to analyse the interactions between IPD factors in the global construction industry based solely on an SLR. While several articles have been written on the factors of IPD implementation globally, the interactions have never been studied before.
Keywords: Integrated project delivery; Challenges; Barriers; Obstacles